Modeling, optimization, and comparable efficacy of T cell and hematopoietic stem cell gene editing for treating hyper‐IgM syndrome. Issue 3 (21st January 2021) - Vavassori, Valentina; Mercuri, Elisabetta; Marcovecchio, Genni E; Castiello, Maria C; Schiroli, Giulia; Albano, Luisa; Margulies, Carrie; Buquicchio, Frank; Fontana, Elena; Beretta, Stefano; Merelli, Ivan; Cappelleri, Andrea; et al.
Abstract: Precise correction of the CD40LG gene in T cells and hematopoietic stem/progenitor cells (HSPC) holds promise for treating X‐linked hyper‐IgM Syndrome (HIGM1), but its actual therapeutic potential remains elusive. Here, we developed a one‐size‐fits‐all editing strategy for effective T‐cell correction, selection, and depletion and investigated the therapeutic potential of T‐cell and HSPC therapies in the HIGM1 mouse model. Edited patients' derived CD4 T cells restored physiologically regulated CD40L expression and contact‐dependent B‐cell helper function. Adoptive transfer of wild‐type T cells into conditioned HIGM1 mice rescued antigen‐specific IgG responses and protected mice from a disease‐relevant pathogen. We then obtained ~ 25% CD40LG editing in long‐term repopulating human HSPC. Transplanting such proportion of wild‐type HSPC in HIGM1 mice rescued immune functions similarly to T‐cell therapy. Overall, our findings suggest that autologous edited T cells can provide immediate and substantial benefits to HIGM1 patients and position T‐cell ahead of HSPC gene therapy because of easier translation, lower safety concerns and potentially comparable clinical benefits. Synopsis: Here we report a comprehensive set of preclinical studies, performed both in vitro on X‐linked hyper‐IgM syndrome (HIGM1) patient‐derived cells and in vivo in HIGM1 mice, which uncovers crucial guiding principles towards clinical translation of CD40LG targeted gene correction in T cells or hematopoietic stem cells (HSC) for the treatment of HIGM1. Efficient targeted integration of a corrective cDNA within the first intron of CD40LG in both T cells and HSC restored regulated CD40L expression with full functionality. Coupling the corrective cDNA to a clinically compatible selector allows enriching, tracking, depleting edited CD4 + T cells and fully rescuing the physiological CD40L surface expression. Adoptive transfer of functional CD4 + T cells or transplantation of a fraction of functional HSC, modelling editing efficiencies achieved in human HSC, reveals similar therapeutic potential in HIGM1 mice. The corrective potential of T cell therapy depends on the engrafted T cell dose and may bypass the requirement for conditioning regimen when cells are sourced from antigen‐primed donors. Abstract : Here we report a comprehensive set of preclinical studies, performed both in vitro on X‐linked hyper‐IgM syndrome (HIGM1) patient‐derived cells and in vivo in HIGM1 mice, which uncovers crucial guiding principles towards clinical translation of CD40LG targeted gene correction in T cells or hematopoietic stem cells (HSC) for the treatment of HIGM1.